USER EXPERIENCE AND EMPLOYEE PERFORMANCE IN E-GOVERNMENT SYSTEM: THE CASE OF SRIKANDI APPLICATION - Yosephine Angelina Yulia; Tri Widianto; Andri Octaviani; Yenni Khristiana (Journal Economics Technology And Entrepreneur, 2025)
This study aims to analyze the influence of user ease of use, system quality, and user satisfaction on employee performance at the Surakarta City Environmental Agency. Data were collected through questionnaires distributed to 35 employees using the SRIKANDI (Sistem Informasi Kearsipan Dinamis Terintegrasi) application. The research method employed Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results demonstrated that user satisfaction had a positive and significant effect on employee performance (p = 0.021), while system quality (p = 0.249) and user ease of use (p = 0.119) did not exhibit significant effects. The Adjusted R Square value of 0.344 indicates that 34.4% of the variation in employee performance can be explained by these three independent variables in the model. These findings emphasize the necessity for further evaluation of the implementation of the latter two variables to optimize employee performance at the Surakarta City Environmental Agency.